2019
DOI: 10.15193/zntj/2019/119/292
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ jakościowych determinant produktów mleczarskich na wybór dyskontów jako miejsca ich zakupu przez młodych nabywców

Abstract: Przemiany zachodzące w sektorze handlowym powodują, że współczesny rynek produktów żywnościowych charakteryzuje się dużą zmiennością i nieprzewidywalnością. Znajomość i zrozumienie czynników kształtujących wybór produktów i miejsc ich zakupu przez nabywców jest ważnym elementem kreowania strategii konkurencyjnej podmiotów działających na danym rynku W Polsce obserwowany jest rozwój sieci dyskontowych. Do niedawna polskich nabywców zachęcały do sklepów dyskontowych przede wszystkim niskie ceny, jednak z czasem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Supermarkets were the preferred place for purchasing milk and processed milk products, as declared by foreign consumers as well [Bytyqi, Muji and Rexhepi 2020]. In the study by Angowski, Kijek and Skrzypek [2019] it was shown that the place where dairy products were purchased were discount stores, but this was mostly where young people shopped.…”
Section: Fig 5 Preferred Place For Buying Innovative Dairy Products [%]mentioning
confidence: 99%
“…Supermarkets were the preferred place for purchasing milk and processed milk products, as declared by foreign consumers as well [Bytyqi, Muji and Rexhepi 2020]. In the study by Angowski, Kijek and Skrzypek [2019] it was shown that the place where dairy products were purchased were discount stores, but this was mostly where young people shopped.…”
Section: Fig 5 Preferred Place For Buying Innovative Dairy Products [%]mentioning
confidence: 99%